The butler - Mackintosh, Clare (Podium Publishing, 2026)
"The South of France is stunning, though not without its imperfections, from pickpockets to burglars to the occasional cold-blooded killer. But in his twenty-five years of service, Baxter--with a spotless reputation as a polished, well-mannered butler--has never run into any issues catering to the ultrawealthy. Until now. Baxter's latest assignment is at Villa Sérénité, where Alec Prescott is hosting a colorful cast of characters, including his ex-wife, his much younger lady friend, and some Hollywood hotshots, after the Cannes Film Festival. But it doesn't take long for a week of sun, wine, and a family birthday celebration to devolve into bickering and backstabbing. And soon, secrets aren't the only thing floating to the surface ... When one of the guests is found dead in the villa's glittering pool, the gendarmes turn to the unflappable Baxter to help determine who's responsible. A good butler is expected to see everything and say nothing--but what if he too becomes a target?"--Page 4 of cover.